CORRELATION OF MATERNAL PARENTING IN TODDLER FEEDING WITH THE INCIDENCE OF STUNTING - Arum Zultiara; Khairunnas; Marniati; Itza Mulyani (RADJA PUBLIKA, 2024)
This study aims to see if there is a relationship between maternal parenting in toddler feeding and the incidence of stunting in Samatiga District, West Aceh Regency. Stunting is a condition of a person's height that is less than normal based on age and sex with a z-score value of less than -2 SD. Problem in this study is the high rate of stunting over the past three years, which is 23.7% of toddlers experiencing stunting from a total of 1,234 toddlers. This study used a cross-sectional survey design. Location and Duration of Research: this research was conducted in Samatiga sub-district in November 2023. Methods: this research is quantitative, with a population of all mothers who have toddlers 1,234 people. Sampling using the quota sampling method, where the pupolation was sampled as many as 93 respondents. Then the data was analyzed using univariate and bivariate and then tested with the Spearman Rank Correlation Model. Results: there is a relationship between feeding parenting patterns and the incidence of stunting in toddlers, namely with a value (Pvalue 0.000 <0.05). Conclusion: there is a relationship between parenting in feeding with the incidence of stunting, it can be proven by the correlation value r 0.567 which means there is a high closeness between parenting in feeding with the incidence of stunting in toddlers. Suggestion: It is hoped that the health center and other related parties will increase the motivation of mothers through education on the importance of good feeding parenting in fulfilling child nutritions